Synthesis and Evaluation of Antimicrobial Activity of Some New Bis Cyclic Imides Linked to Nitrogen Heterocycles - Marouf Al-Azzawi, Ahlam; Sa’adi Hassan, Ahmed (Iraqi Journal of Science, 2023)
In the present work, a series of new bis cyclic imides (pyromellit imides) linked to different nitrogen heterocycles namely (pyridine, pyrimidine, phenazone and quinoline) was synthesized.Synthesis of the new imides was performed via two steps in the first one a series of bis amic acids (pyromellit amic acids) was synthesized via reaction of pyromellitic anhydride with variety of nitrogen heterocyclic primary amines while in the second step the prepared bis amic acids were dehydrated via treatment with acetic anhydride and anhydrous sodium acetate affording the desired imides.The prepared bis Imides were screened for their antimicrobial activity against many types of bacteria and fungi and the results indicated that they possess good inhibition effect against the tested organisms.